Respuesta :

Answer:

3x +13y = 14

6x +11y = -2

Step-by-step explanation:

Substitute the given values into the equations and see which equations are satisfied.

• first set:

3(-4) +13(2) = -12 +26 = 14 . . . . true

6(-4) +11(2) = -24 +22 = -2 . . . . true

You have the answer at this point, but you can check the other choices if you wish.

___

• second set:

4(-4) +5(2) = -16 +10 = -6 ≠ 12 . . . . second set of equations is not the answer

___

• third set:

5(-4) +4(2) = -20 +8 = -12 ≠ 12 . . . . third set of equations is not the answer

___

• fourth set:

10(-4) +3(2) = -40 +6 = -34 ≠ 8 . . . . fourth set of equations is not the answer

Answer:

A

Step-by-step explanation:

I just took the test